2020
DOI: 10.1007/s10557-020-06963-5
|View full text |Cite|
|
Sign up to set email alerts
|

Real-World Dual Antiplatelet Therapy Following Polymer-Free Sirolimus-Eluting Stent Implantations to Treat Coronary Artery Disease

Abstract: Objectives The objective of this post hoc analysis was to analyze real-world dual antiplatelet therapy (DAPT) regimens following polymer-free sirolimus-eluting stent (PF-SES) implantations in an unselected patient population. Methods Patient-level data from two all-comers observational studies ( ClinicalTrials.gov Identifiers: NCT02629575 and NCT02905214) were pooled and analyzed in terms of their primary endpoint. During the data verification… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Using clopidogrel rather than ticagrelor had no effect on MACE, bleeding, and thrombotic events in stable CAD or ACS patients [ 16 , 17 ]. As observed in our study, compared with 6 months of DAPT, 3–6 months of DAPT did not increase the risk of cardiovascular death, myocardial infarction, target vessel revascularization (TVR), definite and probable stent thrombosis, and Bleeding Academic Research Consortium (BARC) 1 year after PF-SES implantation [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using clopidogrel rather than ticagrelor had no effect on MACE, bleeding, and thrombotic events in stable CAD or ACS patients [ 16 , 17 ]. As observed in our study, compared with 6 months of DAPT, 3–6 months of DAPT did not increase the risk of cardiovascular death, myocardial infarction, target vessel revascularization (TVR), definite and probable stent thrombosis, and Bleeding Academic Research Consortium (BARC) 1 year after PF-SES implantation [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two PF-SES’s have an identical polymer-free stent coating, which was intensively studied in the ISAR-TEST 5 trial with a 10-year clinical follow-up [ 6 ]. The devices were studied in different ethnic subpopulations [ 18 ], in lesion morphological subgroups [ 8 ] and dialyzed patients [ 19 ], and were investigated with a focus on real-world dual-antiplatelet therapy (DAPT) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…
Fig. 1 Factors impacting on clinical outcomes after DES procedures (based on Krackhardt et al [ 20 ])
…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to first-generation DP-DES, early-generation BP-DES demonstrated superior safety and a decrease in patient-centered outcomes. However, it has been demonstrated that more recent generations of durable polymers are thromboresistant and even safer than BMS [ 5 ]. PF-DES was developed to provide similar benefits to BMS (lower chances of stent thrombosis) and DP-DES (less risk of lesion revascularization).…”
Section: Introductionmentioning
confidence: 99%